Pengembangan Media Pembelajaran Berbasis Articulate Storyline untuk Meningkatkan Literasi Sains pada Siswa SD Kelas Tinggi - Indri Hidayanti; Astri Sutisnawati; Din Azwar Uswatun (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2021)
This study aims to determine the feasibility of development products Articulate Storyline in the implementation of learning and increasing scientific literacy of high school students. The research method uses the Borgmodel and Gall adapted from Sugiyono. The research subjects were 11th graders of SDN 2 Sukamanah. Methods of data collection using questionnaires, tests, and literacy studies. The research results are based on the results of the validation of experts, practitioners, and student responses. The score obtained from experts and practitioners on the feasibility of content and objectives is 64 (very good), media characteristics/instructional quality is 22.5 (very good), and technical suitability is 41 (good). In student responses, the results obtained on the feasibility of content and objectives are 56.8 with very good category, media characteristics/instructional quality are 16.6 with good category, and technical suitability is 42 with very good category. Scientific literacy of students can be seen from the results of the sample t-test two pairs in which the results are H1 received and H0 is rejected, in other words the existence of enhancing science literacy of high-grade students after using the product development Articulate Storyline.